Role of prostate ultrasonography to predict the efficacy of bipolar prostatectomy in benign prostatic hyperplasia - Ali Ibrahim Ali Yuosef,; Ahmed ElSayed Ibrahm Zeid,; Eslam Shokry AbdelMaksoud,; Tarek Mohamed AbdelBaky,; Hossam ElDeen,; Abdel Hameed Nabeeh, (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the role of prostatic ultrasonography in predicting the clinical outcomes of bipolar transurethral resection of the prostate. Method: The prospective study was conducted at the Urology Department, Kafrelsheikh University Hospital, Cairo, Egypt from December 2018 to June 2019, and comprised male patients complaining of lower urinary tract symptoms due to benign prostatic hyperplasia. The patients were subjected to pelvi-abdominal and transrectal ultrasonography and values were noted for the international prostate symptom score, uroflowmetry, post-void residual urine volume, ejaculatory domain, and the erectile function domain of the international index of erectile function. The safety of the procedure was assessed using the modified Clavien classification of complications. This was followed by cystourethroscopy under spinal anaesthesia, and then by bipolar resection of the prostate by a single experienced urologist. Operating time, length of hospitalisation, intraoperative and postoperative complications, catheterization time, and changes in haemoglobin levels were recorded. All evaluations were done at baseline and postoperatively at 1, 3 and 6 months. Data was analysed using SPSS 21. Results: There were 109 male patients with mean age 65.53±6.27 years, mean body mass index 24.6±1.7kg/m2. Mean total prostate volume at baseline was 86.32±43.61gm (range: 30-195m). There was a significant decrease postoperatively (p<0.001). This was associated with a concomitant improvement of international prostate symptoms score, uroflowmetry and post-void residual urine volume over six-month follow-up (p<0.001 ). Overall, 63(57.8%) subjects were sexually active, and there was no significant difference in the international index of erectile function score at baseline and postoperatively (p>0.05). Conclusion: Prostate ultrasonography can be used as a single investigating tool to evaluate the clinical outcomes after bipolar transurethral resection of the prostate. Keywords: Transurethral resection, Prostate, Prostatic hyperplasia, Erectile, Urinary tract, Ultrasonography, Pelvis.